Selection of Urban Health Equity Assessment and Response Tool indicators using item response theory analysis to assess a city health profile in India - M Siva Durga Prasad Nayak; K A Narayan (Wolters Kluwer Medknow Publications, 2020)
Introduction: City health profile is a useful tool for understanding the health gap and to plan to close the health gap. Of the different tools available to draft a city health profile, the Urban Health Equity Assessment and Response Tool (HEART) developed by the WHO Kobe Centre is one of the best among them. A list of core indicators of the Urban HEART varies from country to country. Aim: In this scenario, an attempt was made with an aim to choose feasible indicators in the Urban HEART to assess a city health profile in Indian setting. Material and Methods: The current study is a cross-sectional observational study conducted among different public health experts in India using an online survey technique. An online survey form was created to collect the public health expert's opinion and sent to public health experts. A total of 105 responses were collected. Statistical Analysis: The average opinion score for each indicator was measured. Item response theory analysis technique was used to calculate the feasibility score to categorize the indicators. Results: The average score of the 60 indicators ranged from 4.54 to 2.77. The feasibility score ranged from 4.13 to − 0.49. Of 60 indicators, 16 indicators were strongly recommended, 41 were recommended, and 3 indicators were optional indicators. Nineteen were highly feasible, 28 feasible, and 13 were less feasible indicators. Conclusion: The Urban HEART can be applied in Indian setting. Data collection can be started with feasible indicators and later can be extended to other indicators.